Oral rehydration solution without bicarbonate. Issue 11 (November 1984) - Islam, M R; Ahmed, S M
Abstract : The efficacy of oral rehydration solution without bicarbonate was compared with World Health Organisation oral rehydration solution in 98 young children in a double blind and randomised clinical trial. These children had varying degrees of dehydration and acidosis caused by acute watery diarrhoea. The mean serum bicarbonate concentration on admission was 13.3 mmol(mEq)/1 in the former and 13.1 mmol(mEq)/1 in the latter group of children. All but three children who received the rehydration solution without bicarbonate were successfully treated; three treatment failures were attributed to persistent vomiting and severe diarrhoea (greater than 10 ml/kg/hour). Correction of acidosis was slower in the non-bicarbonate treated than the control group during the first 24 hours' treatment (P less than 0.001). By 48 hours, however, acidosis was corrected and mean serum bicarbonate had risen to 17.1 mmol(mEq)/1 compared with 18.9 mmol(mEq)/1 in the control group (P greater than 0.05). Some failures due to sustained acidosis and persistent vomiting and diarrhoea should be expected. Oral rehydration solution without bicarbonate may be used where complete formula solution is not available.